2019
DOI: 10.1038/s41467-019-08579-2
|View full text |Cite
|
Sign up to set email alerts
|

The Elongator subunit Elp3 is a non-canonical tRNA acetyltransferase

Abstract: The Elongator complex catalyzes posttranscriptional tRNA modifications by attaching carboxy-methyl (cm5) moieties to uridine bases located in the wobble position. The catalytic subunit Elp3 is highly conserved and harbors two individual subdomains, a radical S-adenosyl methionine (rSAM) and a lysine acetyltransferase (KAT) domain. The details of its modification reaction cycle and particularly the substrate specificity of its KAT domain remain elusive. Here, we present the co-crystal structure of bacterial Elp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 69 publications
7
66
0
Order By: Relevance
“…In zebrafish, we found diminished levels of this modification in morphant zebrafish. Also, recent structural evidence strongly support the Elongator complex function is tRNA modification [36,37]. Altogether, this data strongly indicates that the primary and evolutionarily-conserved function of the…”
Section: Discussionsupporting
confidence: 56%
“…In zebrafish, we found diminished levels of this modification in morphant zebrafish. Also, recent structural evidence strongly support the Elongator complex function is tRNA modification [36,37]. Altogether, this data strongly indicates that the primary and evolutionarily-conserved function of the…”
Section: Discussionsupporting
confidence: 56%
“…S4d-e). 34 The observation that ac4C and mcm5s2U are sensitive to the metabolic state of the cell is consistent with the findings of Balasubramanian and coworkers, who reported that starvation conditions reduced NAT10-dependent ac4C levels in transfer RNA. 35 The ability of ACLY perturbation to influence the acetylation of poly(A)RNA, but not total RNA, suggests inhibitory CoA/acyl-CoAs may interact in a distinct manner with different functional forms of NAT10.…”
Section: Evaluating the Dynamic Activity Of Acetyltransferases In Ressupporting
confidence: 90%
“…However, total protein concentration in the soluble fractions was similar for the three strains (Supplementary Figure S3B). Coupled with similar [ 35 were generated and analyzed by SDS PAGE before (total protein) and after enrichment of aggregates, as described previously [4,29]. Aggregates were isolated twice from each strain.…”
Section: The Absence Of Both Asl Modifications Drastically Increasesmentioning
confidence: 99%
“…These complex modifications are synthesized in multi-step pathways [32] with key enzymes in multi-subunit complexes: the KEOPS complex for t 6 A synthesis [33] and the Elongator complex (Elp1-Elp6) for mcm 5 U [28,34]. While the mechanistic aspects of their synthesis are still being elucidated, most genes involved have been identified [32] and the pathways have been reconstituted fully [23] or partially [35,36] in vitro. This has allowed researchers to dissect the role of these modifications in vivo, where it has become apparent that defects in mcm 5 s 2 U34 and t 6 A37 synthesis in yeast gives rise to very similar phenotypes, including activation of the Gcn4 General Amino Acid Control (GAAC) response independently of Gcn2 and sensitivity to similar stresses [3,29,37].…”
Section: Introductionmentioning
confidence: 99%